2012
DOI: 10.1136/heartjnl-2012-302256
|View full text |Cite
|
Sign up to set email alerts
|

Differences in performance of five types of aortic valve prostheses: haemodynamic assessment by dobutamine stress echocardiography

Abstract: Stentless bioprostheses displayed haemodynamics superior to stented or mechanical prostheses and had the closest performance to a normal, native aortic valve. Stress DSI data, least reliant on variable annulus/valve sizes and flow rates, provided the best haemodynamic discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Several studies have shown that stentless prostheses provide a better hemodynamic performance, especially during exercise, in that the effective orifice area increases as the flow increases . On the other hand, the design of currently available stented valves has improved to such an extent that these valves now provide excellent fluid dynamic performance.…”
mentioning
confidence: 99%
“…Several studies have shown that stentless prostheses provide a better hemodynamic performance, especially during exercise, in that the effective orifice area increases as the flow increases . On the other hand, the design of currently available stented valves has improved to such an extent that these valves now provide excellent fluid dynamic performance.…”
mentioning
confidence: 99%
“…Interestingly, despite a significant improvement in functional classes at 36 ± 12 month follow-up, most of patients developed at least mild PPM, with significant increase in mean prosthetic gradients, reaching an average of 42.3 ± 12.7 mm Hg. 22 Increasing transvalvular gradients under DSE have been reported also by Sezai et al 23 Interestingly, Khoo et al 24 reported on the hemodynamic better performance of stentless over stented prostheses. These authors showed that stentless valve prostheses perform similarly to mildly stenosed native aortic valves under stress, whereas stented and mechanical prostheses resembled the performances of mild-to-moderate stenosis.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, Khoo et al . reported on the hemodynamic better performance of stentless over stented prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Khoo et al 10 present rest and stress echocardiographic evaluation of the haemodynamic performance of five different prosthetic aortic valves and highlight controversies concerning designs associated with the best haemodynamic performance and challenges in assessment with controls for prosthesis size and flow rates. They demonstrate that stentless bioprostheses have superior haemodynamics (both at rest and during pharmacological stress) with parameters equivalent to mild native aortic stenosis (peak gradient 16±1 mm Hg and mean gradient 9±1 mm Hg) while stented bioprosthetic and mechanical valves (in this study a single tilting disc valve) are inferior with haemodynamic performance equivalent to moderate native aortic stenosis (peak gradient 24±3 mm Hg and mean gradient 13±2 mm Hg).…”
Section: Comparative Studiesmentioning
confidence: 99%